Short to Midterm Resultsof Arthroscopic Rotator Cuff Repair in Rajavithi Hospital - Srisuwanporn, MD, Pinij; Kamchatphai, MD, Sittiporn; Panyasakulwong, MD, Roongroj; Cheecharern, MD, Sukrom; Preecha, MD, Weera (Journal of Southeast Asian Orthopaedics, 2022)
Purpose: Arthroscopic rotator cuff repair is the standard treatment for rotator cuff injury. This study aimed to determine functional outcomes after arthroscopic rotator cuff repair and assess the relationships between fatty degeneration, muscle atrophy, tendon retraction and clinical results after surgery. Methods: Forty-six patients with rotator cuff injuries were treated with arthroscopic rotator cuff repair in Rajavithi Hospital between 2006 and 2012. Forty patients (17 men and 23 women) were examined at follow-up ranging from 12 to 96 months (average 46.13 months). Preoperative evaluation included clinical examination, plain radiograph and MRI. Plain radiographs were used to measure acromiohumeral distance, and MRI was used to assess fatty degeneration, muscle atrophy, and tendon retraction. Postoperative evaluations were made to assess pain, muscle power, ability to perform activities of daily living, and measure American Shoulder and Elbow Surgeons (ASES) scores at follow-up. Results: Postoperatively, 33 patients had no pain, while 7 patients still had pain at night and usually took some pain killers. The success of the surgery was assessed using the visual analog scale (0-10), and the mean score was 9.50 (range 5-10). Pain scores decreased from 8.7 preoperatively to 1.1 at follow-up (P<0.05). Average ranges of motion were 173 degrees in flexion, 173 degrees in abduction, and 34 degrees in external rotation. Muscle power increased from 8 N preoperatively to 32 N at follow-up. Mean ASES scores improved significantly from 29.63 preoperatively to 91.27 at follow-up (P<0.05). The mean tendon retraction measurement was 23.17±13.02mm. There were relationships between tendon retraction and fatty degeneration (P=0.007) and between tendon retraction and muscle atrophy (P<0.001). The study was unable to identify any relationships between rotator cuff pathology (fatty degeneration, muscle atrophy, and tendon retraction and postoperative functional outcomes (post operative ASES scores (P=0.146, 0.473, 0.717)), and muscle power (P=0.515, 0.435, 0.484)). Conclusion: Arthroscopic rotator cuff repair reduced pain and improved patients’ ability to carry out dailyactivities. Tendon retraction was related to fatty degeneration and muscle atrophy. No relationship was found between rotator cuff pathology and postoperative functional outcomes.